2012
DOI: 10.1371/journal.pone.0044560
|View full text |Cite
|
Sign up to set email alerts
|

An Internal Model Architecture for Novelty Detection: Implications for Cerebellar and Collicular Roles in Sensory Processing

Abstract: The cerebellum is thought to implement internal models for sensory prediction, but details of the underlying circuitry are currently obscure. We therefore investigated a specific example of internal-model based sensory prediction, namely detection of whisker contacts during whisking. Inputs from the vibrissae in rats can be affected by signals generated by whisker movement, a phenomenon also observable in whisking robots. Robot novelty-detection can be improved by adaptive noise-cancellation, in which an adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 130 publications
(213 reference statements)
2
34
0
Order By: Relevance
“…Ă”Signal conditioningĂ• indicates the importance of early processing of sensory signals to, for instance, distinguish components of the signal that may be due to the organismĂ•s (or robotĂ•s) own movement rather than to contact with the external world. Some neurobiological evidence, and our own modelling work, suggest an important role for the cerebellum in this regard (Anderson, Pearson et al, 2010;Anderson, Porrill et al, 2012).…”
Section: A Control Architecture For Behavioural Integration In Vibrismentioning
confidence: 69%
See 3 more Smart Citations
“…Ă”Signal conditioningĂ• indicates the importance of early processing of sensory signals to, for instance, distinguish components of the signal that may be due to the organismĂ•s (or robotĂ•s) own movement rather than to contact with the external world. Some neurobiological evidence, and our own modelling work, suggest an important role for the cerebellum in this regard (Anderson, Pearson et al, 2010;Anderson, Porrill et al, 2012).…”
Section: A Control Architecture For Behavioural Integration In Vibrismentioning
confidence: 69%
“…In a further extension of our sensory noise cancellation model (Anderson, Porrill et al, 2012) we have shown that the addition of sensory information from the whiskers allows the adaptive filter to learn a more complex internal model that performs more robustly than a forward model based on efference copy signals alone, particularly when the whisking-induced interference has a periodic structure. More generally, our analysis of the whisking noise cancellation scheme reveals that the functional role of the cerebellum may be to learn a forward model of the whisker/follicle dynamics.…”
Section: Figure 8 Herementioning
confidence: 99%
See 2 more Smart Citations
“…Parts of the cerebellar cortex process the whisker sensory information (Bosman et al, 2010) but the functional importance of this activity is still unknown. Interestingly, while the cerebellar inactivation seemed to minimally perturb whiskers' movements, a longer fraction of the total whisking time was spent exploring objects, suggesting a failure to adapt to familiar objects (Anderson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%